Search for third-generation scalar leptoquarks in the t tau channel in proton-proton collisions at root s=8 TeV - Khachatryan, V. (2015)
A search for pair production of third-generation scalar leptoquarks decaying to top quark and tau lepton pairs is presented using proton-proton collision data at a center-of-mass energy of root s=8TeV collected with the CMS detector at the LHC and corresponding to an integrated luminosity of 19.7 fb(-1). The search is performed using events that contain an electron or a muon, a hadronically decaying tau lepton, and two or more jets. The observations are found to be consistent with the standard model predictions. Assuming that all leptoquarks decay to a top quark and a tau lepton, the existence of pair produced, charge -1/3, third-generation leptoquarks up to a mass of 685 GeV is excluded at 95% confidence level. This result constitutes the first direct limit for leptoquarks decaying into a top quark and a tau lepton, and may also be applied directly to the pair production of bottom squarks decaying predominantly via the R-parity violating coupling lambda'(333) .